Situation Report: Hungary, 20 July 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian Press Critical of Romania Coverage of Nixon's Proposed Visit to China Criticism of New Five-Year Collective Agreements Decree on "Moonlighting" The NEM's Influence on Hungarian Culture New Economic Regulators to Control Meat Production Harvest Well Advanced - Good Prospects for Wheat